Zagreb-Type Indices of R-Vertex Join and R-Edge Join of Graphs - Jianxin Wei; Muhammad Imran; Muhamamd Azhar Iqbal; Muhammad Asad Zaighum (Journal of Chemistry)
There are various methods available which are used to search large chemical databases and to predict the physicochemical properties of molecular structures. Using molecular descriptors for this purpose is the simplest of these methods. The Zagreb indices are amongst the oldest molecular descriptors, and their properties have been extensively studied and applied in QSAR/QSPR studies. The Zagreb coindices were recently introduced, attracting the attention of researchers in mathematical chemistry. In this paper, we study Zagreb indices and several other Zagreb-type indices including the general Randić index, sum-connectivity index, F-index, and Zagreb coindices of R-vertex and edge join of two arbitrary graphs.